Avaliação das técnicas de compactação aplicáveis a programas em linguagens funcionais em arquiteturas superescalares - Silva, Mariza Bigonha Andrade da (1997)
The need for fasters processors and effcient executions has motivated the designers of new architectures and methods for code otimization. This paper presents important aspects of the superscalar architectures functional languages and the compaction methods used with imperative languages programs. It also presents a compaction method known as pessimistic algorithms based on software pipelining_ The method makes a global compaction of the program and can be applied to programs written in functional languages can be extended to the compaction of general recursive functions and can be used with superscalar machines.